2020
DOI: 10.3390/molecules25040893
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Resveratrol, β-Lapachone and Their Analogues

Abstract: This review aims to explore the potential of resveratrol, a polyphenol stilbene, and beta-lapachone, a naphthoquinone, as well as their derivatives, in the development of new drug candidates for cancer. A brief history of these compounds is reviewed along with their potential effects and mechanisms of action and the most recent attempts to improve their bioavailability and potency against different types of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 157 publications
1
31
0
Order By: Relevance
“…Another study also confirmed a radioprotective role of epicatechin in human keratinocyte HaCaT cells and in Sprague-Dawley rats via ROS regulation and JNK and p38 pathway alterations [227]. [228][229][230]. ARQ 761, a β-lapachone analogue, has completed a phase I clinical trial (clinical trial number: NCT01502800) in advanced solid tumors.…”
Section: Polyphenolsmentioning
confidence: 75%
See 1 more Smart Citation
“…Another study also confirmed a radioprotective role of epicatechin in human keratinocyte HaCaT cells and in Sprague-Dawley rats via ROS regulation and JNK and p38 pathway alterations [227]. [228][229][230]. ARQ 761, a β-lapachone analogue, has completed a phase I clinical trial (clinical trial number: NCT01502800) in advanced solid tumors.…”
Section: Polyphenolsmentioning
confidence: 75%
“…β -Lapachone (3,4-dihydro-2,2-dimethyl-2H-naphthol (1,2-b) pyran-5,6-dione (C 15 H 14 O 3 )) is a natural naphthoquinone, originally an isomer of lapacho, obtained from the bark of the purple Ipe in South America. Various studies have demonstrated that β -lapachone can induce cell death in solid cancers including esophageal and oral cancers [ 228 230 ]. ARQ 761, a β -lapachone analogue, has completed a phase I clinical trial (clinical trial number: NCT01502800 ) in advanced solid tumors.…”
Section: Natural Herbs Effectively Modulating Ros Are Important Drmentioning
confidence: 99%
“…Specifically, a certain association has been observed between alcohol consumption and the risk of developing different types of cancer, regardless of the amount consumed [15]. On the other hand, some authors have reported that alcohol consumption is associated with a decreased incidence of cancer because of its stilbenoid content [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to rapid and extensive metabolism, its bioavailability is poor. A growing body of evidence indicates that various chemical modifications may significantly improve resveratrol's bioavailability and potency against different types of cancer [12]. Mayhoub and co-workers replaced the trans stilbene ethylenic bridge of the resveratrol scaffold with a 1,2,4-thiadiazole heterocycle and next modified the substituents on the two aromatic rings and evaluated cytotoxicity of these compounds against human breast cancer MCF-7 cell line.…”
Section: Derivatives Of 124-thiadiazolementioning
confidence: 99%